The Bacterial and Fungal Microbiota of Saccharina latissima (Laminariales, Phaeophyceae) - Tourneroche, Anne; Lami, Raphaël; Burgaud, Gaëtan; Domart-Coulon, Isabelle; Li, Wei; Gachon, Claire; Gèze, Marc; Boeuf, Dominique; Prado, Soizic (Frontiers in Marine Science, 2020)
The sugar kelp Saccharina latissima dominates many temperate coastal ecosystems, plays key ecological roles and presents important economic potential. However, its microbiota remains poorly investigated, although it could play an important role in algal fitness. In this study, we combined high throughput Illumina-based DNA sequencing and Fluorescence In Situ Hybridization to perform a culture-independent investigation of the S. latissima bacterial and fungal microbiota. Up to 600 bacterial and 100 fungal Amplicon Sequence Variants were identified per algal individual, revealing diverse bacterial and fungal communities associated to S. latissima. Overall, bacterial communities were dominated by Proteobacteria, Actinobacteria and Bacteroidetes, in particular Hyphomonadaceae and Cyclobacteriaceae. Fungal communities were dominated by Ascomycota and Basidiomycota, in particular Mycosphaerellaceae, Psathyrellaceae and Bulleribasidiaceae. Our results also revealed a variable distribution of S. latissima microbiota, as two adjacent tissue samples typically contained distinct fungal and bacterial assemblages, and CARD-FISH analysis detected microbial endosymbionts (with a few epibionts). Complementary analyses showed that despite achieving a good sequencing coverage for each tissue sample, the unexpected diversity and variability of ASVs made the definition of a core fungal and bacterial microbiota difficult, and highlights novel avenues to overcome the limitations of current surface-sterilization and metabarcoding protocols.